Studi Eksploratif Tentang Potensi Pengembangan Perguruan Tinggi Berbasis Wakaf - Trisna Herlinda; Randy Heriyanto (Akuntansi dan Manajemen, 2017)
This study aims to look at the potential for the development of waqf-based universities in West Sumatra. This study begins with the problem of the magnitude of potential waqf in Indonesia, especially West Sumatra, which has not been managed optimally. This condition is a great opportunity for the education sector to be able to transform and develop waqf as a financing alternative to higher education. Waqf can be managed by producing and investing in real sector and investment in Islamic financial institutions. Many financing models can be done with waqf assets, but must pay attention to sharia-compliant principles. The research data was collected through in-depth interviews with several Islamic university leaders and various waqf stakeholders. The results of this study indicate that so far, no information has been obtained regarding the true potential of waqf in West Sumatra because the data collected from each waqf manager is still not optimal and requires a long time. But what needs to be done now is to optimize waqf management and increase socialization especially for money waqf.